Software Engineering Frameworks Used for Serious Games Development in Physical Rehabilitation: Systematic Review - Jorge Fernando Ambros-Antemate; María Del Pilar Beristain-Colorado; Marciano Vargas-Treviño; Jaime Gutiérrez-Gutiérrez; Pedro Antonio Hernández-Cruz; Itandehui Belem Gallegos-Velasco; Adriana Moreno-Rodríguez (JMIR Publications, 2021)
BackgroundSerious games are a support in the rehabilitation process for treating people with physical disabilities. However, many of these serious games are not adapted to the patient's needs because they are not developed with a software engineering framework with a set of activities, actions, and tasks that must be executed when creating a software product. Better serious games for rehabilitation will be developed if the patient and therapist requirements are identified, the development is planned, and system improvements and feedback are involved. The goal is that the serious game must offer a more attractive environment, while maintaining patient interest in the rehabilitation process. ObjectiveThis paper submits the results of a systematic review of serious games in physical rehabilitation identifying the benefits of using a software engineering framework. MethodsA systematic research was conducted using PubMed, PEDro (Physiotherapy Evidence Database), IEEE Xplore, ScienceDirect, ACM Digital Library, Mary Ann Liebert, Taylor & Francis Online, Wiley Online Library, and Springer databases. The initial search resulted in 701 papers. After assessing the results according to the inclusion criteria, 83 papers were selected for this study. ResultsFrom the 83 papers reviewed, 8 used a software engineering framework for its development. Most of them focused their efforts on 1 or more aspects, such as data acquisition and processing, game levels, motivation, therapist supervision. ConclusionsThis systematic review proves that most of the serious games do not use a software engineering framework for their development. As a result, development systems overlook several aspects and do not have a standardized process, eventually omitting important implementation aspects, which impact the patient's recovery time.